Immune-related Adverse Effects and Outcome of Patients With Cancer Treated With Immune Checkpoint Inhibitors - Fiala, Ondrej; Sorejs, Ondrej; Sustr, Jan; Kucera, Radek; Topolcan, Ondrej; Finek, Jindrich (Anticancer research, 2020)
Immunotherapy based on immune checkpoint inhibitors (ICIs) represents a novel anticancer treatment strategy. Monoclonal antibodies targeting cytotoxic T-lymphocyte antigen-4 (CTLA4), programmed cell death-1 receptor (PD1) and programmed cell death-1 ligand (PD-L1) have shown efficacy and safety in the treatment of various malignancies. Some of them have recently found their place in a routine clinical practice, while others are at different phases of clinical trials. Treatment with ICIs may be accompanied by undesirable impairment of immunotolerance to non-tumoural tissues, leading to a specific side-effect also called immune-related adverse events (irAE). There is an increasing body of evidence that the development of irAEs is associated with a beneficial effect of immunotherapy, thus it has become a hot topic in the field of clinical oncology. This review is focused on data from recently published studies evaluating the association between irAEs and outcome of patients with cancer treated with ICIs.
Keywords: Drug-Related Side Effects and Adverse Reactions; checkpoint inhibitor; nádory; efficacy; antigeny CD279; Humans; výsledek terapie; adverse effects; Programmed Cell Death 1 Receptor; review; lidé; imunoterapie; nežádoucí účinky léčiv; Immunotherapy; Treatment Outcome; Neoplasms; outcome